Technical nursing course at PROFAE-Ceará: an analysis from the graduates' perspective - Costa, Carmem Cemires Cavalcante; Bezerra Filho, José Gomes; Machado, Márcia Maria Tavares; Machado, Maria de Fátima Antero Sousa; Jorge, Antônia Cristina; Castro, Tânia Maria Saunders de (Revista da Escola de Enfermagem da USP, 2009)
This study aimed to analyze PROFAE's technical Nursing course from the perspective of the students that had completed the course regarding the identification of strengths and weaknesses they identified during the program. This exploratory, qualitative-based descriptive study was carried out with graduates of the Public Healthcare School of Ceará, who had completed the course. Two focal groups composed of 21 graduates were organized in the months of May and June 2007. The content analysis was used for the comprehension of the discourses. Results indicated that the course provided the graduates with a great deal of knowledge, thus positively affecting their lives and transforming them into agents of change in their work contexts. The study analyzed the curriculum, the methodology, the textbooks and other available materials, as well as the professors. The reported weaknesses were training field limitations, the length of the course, and the sponsorship management. The present assessment represents an important tool for the development of the course, generating an opportunity for the improvement of the proposal.